2017
DOI: 10.1177/1010428317715039
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure of resveratrol induces reactive superoxide species–independent apoptosis in murine prostate cells

Abstract: Nitric oxide, a signaling molecule, inhibits mitochondrial respiration by binding with cytochrome c oxidase, resulting in elevated production of reactive superoxide species (reactive oxygen and nitrogen) in the mitochondria and increased susceptibility to cell death. Generation of mitochondrial superoxide species can be suppressed by natural compounds such as resveratrol, a dietary polyphenol found in the skin of red fruits. In various cancer cells, resveratrol shows anti-oxidant and cancer preventive properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Cell death of tachyzoites. Since resveratrol has been considered to alter the signaling pathway for apoptosis in many tumor cells (24,25) and we already saw its potential for RH tachyzoite inhibition, we were interested in examining whether it could promote phosphatidylserine (PS) exposure as a marker of the initiation of the early apoptotic process. We stimulated RH tachyzoites with resveratrol (50 M) for 12 h, followed by PS detection through annexin V-fluorescein isothiocyanate (FITC) labeling.…”
Section: Resultsmentioning
confidence: 99%
“…Cell death of tachyzoites. Since resveratrol has been considered to alter the signaling pathway for apoptosis in many tumor cells (24,25) and we already saw its potential for RH tachyzoite inhibition, we were interested in examining whether it could promote phosphatidylserine (PS) exposure as a marker of the initiation of the early apoptotic process. We stimulated RH tachyzoites with resveratrol (50 M) for 12 h, followed by PS detection through annexin V-fluorescein isothiocyanate (FITC) labeling.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the effects of polyphenols on ΔΨm, growing evidence suggests a beneficial effect, but the literature is somewhat inconsistent. While Qi et al report an improved membrane potential after treatment with tea polyphenols in SH-SY5Y cells [85] or an increased potential through resveratrol in rats with diabetic cardiomyopathy [86], Kumar et al found a disrupted ΔΨm after prolonged exposure to resveratrol in murine prostate cancer cells [87].…”
Section: Discussionmentioning
confidence: 99%
“…This article provides an overview of recent findings about the anti-PCa activity of different natural compounds (Figure 2, Table 1). [47][48][49][50][51][52][53][54]80,100,107,123,124,[135][136][137][138][139]161,163,164,186,190,191,212] The use of phytochemicals for PCa management offers several advantages. Firstly, natural products are safe and well tolerated, as well as usually economically affordable.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while apigenin, luteolin, genistein, and celastrol inhibited the proteasomal activity and caused ubiquitinated protein accumulation in different PCa cell lines [154][155][156], quercetin, curcumin, silibinin, and tannic acid induced endoplasmic reticulum (ER) stress [157][158][159][160], a condition where unfolded/misfolded proteins accumulate in the ER lumen and promote the activation of distinct pro-death cascades, including the double-stranded RNA-dependent protein kinase PKR-like ER kinase (PERK)/eukaryotic initiation factor 2α (eIF2α)/activating transcription factor 4 (ATF4)/C/EBP homologous protein (CHOP) pathway and the inositol-requiring enzyme 1α (IRE1)/c-Jun N-terminal kinase (JNK)/p38 MAPK cascade [161]. Notably, curcumin-and silibinin-mediated ER stress was associated with generation of reactive oxygen species (ROS) and redox homeostasis alteration [159,162], which were also observed in resveratrol-and sulforaphane-treated PCa cells [163][164][165][166].…”
Section: Natural Compounds Inducing Canonical and Non-canonical Cell mentioning
confidence: 99%